UPAYA PENINGKATAN SIKAP PROFESIONAL GURU MELALUI PENINGKATAN KEBIASAAN MEMBACA - Ambarita, Biner (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: An Attempt to Improve Teachers’ Professional Attitudes through Reading Habit Improvement. This study aims to investigate the effectiveness of the reading habit in increasing the professional attitude of history teachers in senior high schools (SHSs) in Medan City. This was a quasi-experimental study involving history teachers in SHSs in Medan City. The data were collected by using questionnaires, one to measure the level of teachers’ reading habit and one to measure the level of teachers’ professional attitude. The data were analyzed using the analysis of covariance. The results of this study showed that the average level of teachers’ reading habit increased, followed by the increase of the level of teachers’ professional attitude. It can be concluded that teachers’ condition after the treatment is better. In other words, the reading habit is effective to increase the professional attitude of history teachers in SHSs in Medan City. Keywords: reading habit, professional attitude